Book Review: Toffee Apples and Togas by Rita Roberts - J. Katerina Katerina Dvoráková (EXARC Journal)
Although Marcus Gavius Apicius was a brilliant observer and author, he was no cook, this is possible to recognise even after 2000 years... Only people truly knowledgeable in cooking, and also those who love to experiment, can cook according to the literary translation of Apicius ( Beranová – Řešátko 2000, 7 and 88, my own translation).